The Relationship Between Interpersonal Communication Of Married Couples And Decision Making To Participate In Mow In The Boarding Room Of Merauke Hospital - Elsa Irianja; Shanty Natalia; Retno Palupi Yonni Siwi; Tety Ripursari (Universitas STRADA Indonesia, 2024)
Indonesia according to BKKBN in 2019 there were around 68 active participants in KB MOW, in 2021 there were 3 active participants in KB MOW, and in 2020 there were 57 active participants in KB MOW. According to the Papua Provincial BKKBN, the percentage of users of the MOW family planning method in Papua Province in 2021 was 4,530 participants, in 2021 there were 4493 participants, and in 2022 there were 4660 active family planning participants. For the Merauke region itself, there were 57 mow participants within 1 year. The use of family planning MOW at the hospital itself has 57 participants within 1 year. To determine the relationship between interpersonal communication between married couples and decision making to participate in MOW in the Ponek Room of Merauke Hospital. This study uses a cross-sectional research method , which is a study where the variables that include the effect are observed at the same time. The sample technique used was a total sampling of 30 people. The data techniques were included in univariate analysis using frequency distribution and bivariate analysis using statistical calculations of the SPSS 23 program. The results of this study show that the value of p = 0,0.03<0.005, this means that there is a relationship between the Interpersonal Communication Relationship of Married Couples and the Decision Making of Mow Participation in the Ponek Room of Merauke Hospital. The Relationship between Interpersonal Communication of Married Couples and Decision Making on Mow Participation in the Ponek Room of Merauke Hospital.